CONTEXTUALIZATION OF FRAGMENTS OF WALL PAINTING FROM 1654 IN THE CATHOLICOON OF SAINT NICHOLAS OF THE BUKOVA MONASTERY NEAR NEGOTINE (DIOCORITY OF TIMOČKA) On the occasion of 190 years since the restoration of the monastery kynovija (Heritage, 2025)
Based on three fragments of wall painting from 1654 in the cathedral church of St. Nicolas of the Bukovo Monaster, an attempt is made to determine the context of their creation as a potential contribution to completing the few facts related to the history of this sacred locus. A fragment from the northern conch with the figure of a younger beardless man in civilian Bizantine costume with a cross in his hand indicates post  Byzantine achievements, particularly cherished in monastic environments. The picture of Bukovo as a monastery during the period of decoration with the aforementioned frescoes is completed by the composition „To You, O Blessed One, All Creation Rejoices….“ Connected to the theme of the himn Akathist to the Most Holy Theotokos, the practice of regular reading of which was developed precisely in monastic communities. The third fragment with the depiction of the Archangel Michael opens the question of the dedication of the cathedral church of St. Nicholas, i.e.possible changes in that sense. Since it was concluded on the basis of the presented analogies that the Bukovo monastery potentially represents a striking point on the paths of church painting in the aforementioned period, the issue of jurisdiction was also considered based on the then affiliation to the Vidin Metropolis of the Patriarchate of Constantinople, which, along with other indicators, suggests a connections with the then Athos achievements.
Keywords: Bukovo Monastery, catholicon, martyrs, Akathist to the Most Holy Theotokos the Intercessor, Thee, the All Graceful Rejoices, jurisdiction, fragments